Phase-field study for the splitting mechanism of coherent misfitting precipitates in anisotropic elastic media - Cha, PR; Yeon, DH; Chung, SH (PERGAMON-ELSEVIER SCIENCE LTD, 2005)
Through a phase-field study upon the splitting behavior and morphological evolution of coherent precipitates, we show that an interface instability driven by elastic anisotropy and a diffusion field can generate elastically induced splitting during diffusional phase transition. Particle splitting is triggered by interface grooving which advances by penetrating grooves into the interior of the particle. The sequential evolution of shapes during the splitting process is in good agreement with previous experiments. (c) 2005 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: NICKEL-BASE ALLOYS; NI-AL ALLOYS; MICROSTRUCTURAL EVOLUTION; INTERACTION ENERGY; STRESSED SOLIDS; MODEL; MORPHOLOGY; STABILITY; KINETICS